Good Living and Social Management: in Pursuit of a Decolonial Dialogue in the Management Studies Field - Cunha, Eduardo Vivian da; Sousa, Washington (Organizações & Sociedade, 2025)
Scholars often point out the need of building a Brazilian and Latin American way of thinking in opposition to the Eurocentric, colonial thinking. Based on this premise, the aim of the current study is to encourage reflections about decoloniality through the conciliation of Good Living practices and ideas – based on the original Ecuadorian concept of it – and Social Management attributes. This reflection was mediated by references that mainly derive from Latin American debates about decoloniality and Good Living, as well as from Brazilian debates about critical management studies and social management. In order to do so, confluences and divergences around worldviews contemporaneously built from the indigenous idea of Good Living, shared by Social Management, were synthesized in this study. The herein performed exercise enabled seeing similarities between the worldview encompassed by Good Living and that deriving from the Brazilian debate about Social Management, although with differences limited to applications in different periods-of-time and contexts, as well as in some epistemological premises. Including the decolonial debate in the Social Management scope can help broadening its understanding and action horizon, without compromising or replacing the construction process carried out to date. Finally, a research agenda aimed at broadening this debate should be developed.